Melatonin Enhances the Therapeutic Effect of Plasma Exosomes Against Cerebral Ischemia-Induced Pyroptosis Through the TLR4/NF-κB Pathway - Wang, Kankai; Ru, Junnan; Zhang, Hengli; Chen, Jiayu; Lin, Xiao; Lin, Zhongxiao; Wen, Min; Huang, Lijie; Ni, Haoqi; Zhuge, Qichuan; Yang, Su (Frontiers in Neuroscience, 2020)
Introduction Ischemic stroke-induced inflammation and inflammasome-dependent pyroptotic neural death cause serious neurological injury. Nano-sized plasma exosomes have exhibited therapeutic potential against ischemia and reperfusion injury by ameliorating inflammation. To enhance its therapeutic potential in patients with ischemic injury, we isolated exosomes from melatonin-treated rat plasma and assessed the neurological protective effect in a rat model of focal cerebral ischemia. Methods Basal plasma exosomes and melatonin-treated plasma exosomes were isolated and intravenously injected into a rat model of focal cerebral ischemia. Neurological recovery was evaluated by determining the modified neurological severity score (mNSS), infarct volume, and brain water content. Pyroptosis in the ischemic cortex was detected through dUTP nick-end labeling (TUNEL) assay, lactate dehydrogenase (LDH) release, and gasdermin D (GSDMD) cleavage. NLRP3 inflammasome assembly and global inflammatory cytokine secretion were detected by enzyme-linked immunosorbent assay (ELISA) and Western blot assay. In immunized Sprague–Dawley rats, microglia pyroptosis was determined through a positive percentage of IBA1+ and caspase-1 (p20)+ cells. Finally, the microRNA (miRNA) profiles in melatonin-treated plasma exosomes were analyzed by exosome miRNA microarray analysis. Results Melatonin treatment enhanced plasma exosome therapeutic effects against ischemia-induced inflammatory responses and inflammasome-mediated pyroptosis. In addition, we confirmed that ischemic stroke-induced pyroptotic cell death occurred in the microglia and neuron, while the administration of melatonin-treated exosomes further effectively decreased the infarct volume and improved recovery of function via regulation of the TLR4/NF-κB signaling pathway. Finally, the altered miRNA profiles in the melatonin-treated plasma exosomes demonstrated the regulatory mechanisms involved in neurological recovery after ischemic injury. Conclusion This study suggests that nano-sized plasma exosomes with melatonin pretreatment might be a more effective strategy for patients with ischemic brain injury. Further exploration of key molecules in the plasma exosome may provide increased therapeutic value for cerebral ischemic injury.